PERKEMBANGAN KEPRIBADIAN TOKOH THORFINN DALAM ANIME VINLAND SAGA KARYA MAKOTO YUKIMURA - I Putu Agus Yoga Ambara Putra; NI PUTU, CANDRA LESTARI; I Made Budiana (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2026)
Anime Vinland Saga.” The purpose of this study is to examine the development of Thorfinn’s personality and the factors that influence that development. The method used in this study is a qualitative descriptive method, with the theories applied being Erik Erikson’s Theory of Development, Wallek and Warren’s Literary Psychology Theory, and Judith Herman’s Trauma Theory. Analysis using these theories revealed that Thorfinn in the anime Vinland Saga experiences the Industry vs. Inferiority, Identity vs. Identity Confusion, and Intimacy vs. Isolation stages throughout the first and second seasons of Vinland Saga. Thorfinn undergoes a psychological transformation through the stages of trauma awareness, guilt, and personality reconstruction, until he reaches an advanced stage of intimacy characterized by a desire to protect life without violence.